2015
DOI: 10.1038/srep09956
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of AKT/mTOR and MDM2 enhances Glioblastoma Multiforme cell apoptosis and differentiation of cancer stem cells

Abstract: The poor prognosis of Glioblastoma Multiforme (GBM) is due to a high resistance to conventional treatments and to the presence of a subpopulation of glioma stem cells (GSCs). Combination therapies targeting survival/self-renewal signals of GBM and GSCs are emerging as useful tools to improve GBM treatment. In this context, the hyperactivated AKT/mammalian target of the rapamycin (AKT/mTOR) and the inhibited wild-type p53 appear to be good candidates. Herein, the interaction between these pathways was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 48 publications
8
70
0
Order By: Relevance
“…Inhibition of these proteins, as well as MAPK/ERK, is critical for induction of apoptosis (12,51,52,101). Furthermore, other studies indicate that treatments with targeting of the Pi3K/Akt/mTOR pathway and the MAPK/ERK protein induce early and late apoptosis (102)(103)(104), as also obtained in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Inhibition of these proteins, as well as MAPK/ERK, is critical for induction of apoptosis (12,51,52,101). Furthermore, other studies indicate that treatments with targeting of the Pi3K/Akt/mTOR pathway and the MAPK/ERK protein induce early and late apoptosis (102)(103)(104), as also obtained in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…As depicted in Figure 3 (panel a and b), the PL precursor strongly enhanced the conversion of LC3 I to LC3II, as demonstrated by the increase of the LC3 II/LC3 I ratio. To confirm these data, a western blot analysis of the autophagic protein p62 [22] was performed, using the mTOR inhibitor [23,24] everolimus as a positive control. GPE was proven to significantly augment p62 accumulation, even to a greater extent than everolimus (Figure 3c,d).…”
Section: Gpe Induced Autophagy In Human Hippocampal Neuronsmentioning
confidence: 99%
“…Adult hippocampal neurons were seeded in 6-multiwell plates (1 × 10 5 cells/well) and incubated with saline buffer (control cells) or 500 µM GPE for seven days. In selected experiments, the mTOR inhibitor everolimus (50 nM) was used as positive control of autophagy induction [23,24].…”
Section: Measurement Of Autophagic Inductionmentioning
confidence: 99%
“…Daniele et al [270] (2015) demonstrated that a combined inhibition of Mdm2 and Mdm2 stimulating the AKT/mTOR pathway using inhibitors ISA27 and FC85, respectively, enhanced glioblastoma multiforme (GBM) cell apoptosis and differentiation of CSCs. In MEFs, Wienken et al (2016) [271] demonstrated that efficient iPSC generation is dependent on Mdm2 in absence of p53.…”
Section: Therapeutic Strategies To Restore Wtp53 Function In Cscsmentioning
confidence: 99%